2019
DOI: 10.3390/rs11050529
|View full text |Cite
|
Sign up to set email alerts
|

Kernel-Based Nonlinear Spectral Unmixing with Dictionary Pruning

Abstract: Spectral unmixing extracts subpixel information by decomposing observed pixel spectra into a collection of constituent spectra signatures and their associated fractions. Considering the restriction of linear unmixing model, nonlinear unmixing algorithms find their applications in complex scenes. Kernel-based algorithms serve as important candidates for nonlinear unmixing as they do not require specific model assumption and have moderate computational complexity. In this paper we focus on the linear mixture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…11 Kernelbased unmixing methods consider interactions among endmembers, 12 and the nonlinear unmixing issue is transformed into a linear unmixing problem by mapping endmembers to a high-dimensional feature space. 13,14 For the issue of identifying sources of water pollution, the turbidity of surface water changes within a specific range due to its exposure to an open environment. In the previous study, we found that the turbidity of surface water influences the spectral mixing mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Kernelbased unmixing methods consider interactions among endmembers, 12 and the nonlinear unmixing issue is transformed into a linear unmixing problem by mapping endmembers to a high-dimensional feature space. 13,14 For the issue of identifying sources of water pollution, the turbidity of surface water changes within a specific range due to its exposure to an open environment. In the previous study, we found that the turbidity of surface water influences the spectral mixing mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the nonlinear mixing model, several spectral unmixing methods based on the kernel function are currently proposed . Kernel-based unmixing methods consider interactions among endmembers, and the nonlinear unmixing issue is transformed into a linear unmixing problem by mapping endmembers to a high-dimensional feature space. , …”
Section: Introductionmentioning
confidence: 99%